Theoretical analysis of photoparametric amplifier - Mohammed Elbireki, Majdi Farag (2010)
A fundamental requirement in the design of an optical receiver is the achievement of high sensitivity and broad bandwidth. These two features are very important in getting reliable system. In this project a receiver circuit based on Photo parametric Amplifier (PPA), which is one of the alternative for receiver detection and amplification techniques is fully described. The PPA mode of operation involves optical detection and amplification within a single device. It is able to provide selectivity and sensitivity at the same time, as required for wireless optical communications. The most common problem that any communication system might face is the noise which must be eliminated or at least reduce it. In order to reduce the noise, filters have been implemented before the signal is passing into an amplifier. In this project Up converter has been placed at the transmitter circuit in order to obtain high frequency, while at the receiver side, filters has been placed with Down converter to obtain the desired frequency. The first method is to use Matlab software in implement is the Up and Down converters circuits at the receiver. The second method is to use Optiwave software in implement is the photo parametric amplifier circuit. Photo diode PIN type has been used to detect any coming signal at the receiver circuit. Results showed that the output signal has been improved; with more strength power and noise reduction which showe that photo parametric amplifier is more reliable and suitable to be used in wireless optical communication system.